Recombinant coagulation factor VIIa—a novel haemostatic agent in scoliosis surgery? - Kolban, Maciej (Springer-Verlag, 2005)
Spinal fusion surgery in children and adolescents with idiopathic scoliosis is often associated with severe haemorrhage. Recombinant coagulation factor VIIa (rFVIIa) has previously been shown to be an effective haemostatic treatment for severe bleeding associated with a variety of coagulopathic and non-coagulopathic indications. The aim of this retrospective study was to assess the safety and haemostatic efficacy of rFVIIa in a series of 26 consecutive adolescent patients with scoliosis (22 females; mean age 16.6 years) undergoing correctional surgery. A second series of 26 consecutive patients (20 females; mean age 16.2 years) who received standard therapy during surgery, represented historical controls. Blood loss, transfusion requirements, duration of surgery, and peri-operative measurements of coagulation parameters were compared between the two groups. Intra-operative and combined intra-operative and post-operative blood losses were significantly smaller in the rFVIIa-treatment group than in the historical controls (P=0.003 and 0.032, respectively); rFVIIa-treated patients also demonstrated significantly reduced blood loss per vertebral segment fused (P=0.032) and per hour of surgery (P<0.001). Intra-operative requirements for packed red blood cells were also significantly lower in the treatment group (P=0.042). Patients in the treatment group demonstrated rapid and maintained reduction of prothrombin time and international normalised ratio; values among rFVIIa-treated patients remained significantly lower than those in the control group at all time points evaluated (P<0.001). There were no deaths and no adverse events. These results suggest that rFVIIa is a safe and effective haemostatic agent for use during spinal fusion surgery in adolescent patients with idiopathic scoliosis; however, further research and randomised, placebo-controlled trials are needed to confirm these findings.